Enhanced immobilization of cadmium, lead, and antimony with improved soil fertility using sulfate-reducing bacteria@nano zero-valent iron-modified biochar: coupled chemisorption and microbial mechanisms - Peng, Shirui; Ya, Fengshuo; Yin, Juan; Liao, Changjun; Qin, Dangling; Lian, Jiapan; Li, Hong; Wang, Hailong; Xue, Jianming; Yang, Xiaoe; Lin, Hongfei; Chen, Jiancheng; et al. (Frontiers in Microbiology, 2026)
IntroductionSoil co-contamination with cadmium (Cd), lead (Pb), and antimony (Sb) poses significant environmental and health risks, highlighting the need for effective remediation strategies. Sulfate-reducing bacteria (SRB) are promising for bioremediation, but require optimization to improve effectiveness.MethodsHere, we developed SRB@nZVI@BC, a novel composite integrating SRB, nano zero-valent iron-modified biochar (nZVI@BC), and sodium alginate (SA). Its optimal preparation conditions were identified as 2% SA, 2% CaCl2, 30% SRB solution, and 0.1% nZVI@BC based on mass transfer performance, mechanical strength, and sulfate reduction rate.ResultsThe application of SRB@nZVI@BC increased the proportion of stable forms of Cd, Pb, and Sb in soil and achieved removal efficiencies of 60.22%–63.93% for Cd, 57.13%–59.45% for Pb, and 56.02%–70.37% for Sb in leachate. Compared to alone SRB treatment, SRB@nZVI@BC significantly enhanced SRB activity, promoting sulfur cycling and the generation of S2−, thereby facilitated heavy metal precipitation as insoluble sulfides. SRB@nZVI@BC could improve the adsorption capacity of soil for heavy metals by activating the oxygen-containing functional groups such as C-O-C. Moreover, SRB@nZVI@BC reshaped the soil microbial community by enriching sulfate-reducing genera such as Desulfosporosinus and Desulfitobacterium, driving heavy metal transformation and stabilization. The composite further enhanced soil nutrient availability (N, P, K) and increased enzyme activities, contributing to soil fertility recovery.DiscussionOverall, SRB@nZVI@BC provides an eco-friendly solution for stabilizing multi-metal-contaminated soils and promoting the restoration of barren lands through synergistic adsorption and biomineralization.